Low carbohydrate high fat (LCHF) diets and endurance performance. - Pyke, A. (Journal of Australian Strength and Conditioning, 2017)
Considerable hype regarding the use of low carbohydrate high fat diets has emerged recently but has been researched for ~ 40 years. The basis of this diet involves the "fat adaptation" of an athlete leading to a hypothesized ability to utilize fat at the preservation of muscle glycogen. In theory, this could improve endurance performance given muscle glycogen is limited and its decrease is a contributor to fatigue. This review was conducted by searching relevant textbooks on clinical and practical sport nutrition followed by PubMed, Human Kinetics, Google Scholar and the International Journal of Sport Nutrition and Exercise Metabolism. The results from this literature review yielded a total of 17 research articles regarding low carbohydrate high fat diets which was further broken down into studies that involved carbohydrate restoration periods as well. Overall, research indicated no performance benefit from following a low carbohydrate high fat diet, with high intensity exercise being severely impaired as well as a reduced ability of the immune system and impaired carbohydrate oxidation. Essentially, low carbohydrate high fat diets may have use for sedentary individuals, but are discouraged for athletes in endurance sports